Enhanced β-carotene production in Yarrowia lipolytica through the metabolic and fermentation engineering. (13th April 2023) - Jing, Yiwen; Wang, Jingnan; Gao, Haiyan; Jiang, Yujia; Jiang, Wankui; Jiang, Min; Xin, Fengxue; Zhang, Wenming
Abstract:  : β-Carotene is a kind of high-value tetraterpene compound, which shows various applications in medical, agricultural, and industrial areas owing to its antioxidant, antitumor, and anti-inflammatory activities. In this study, Yarrowia lipolytica was successfully metabolically modified through the construction and optimization of β-carotene biosynthetic pathway for β-carotene production. The β-carotene titer in the engineered strain Yli-C with the introduction of the carotenogenesis genes crtI, crtE, and crtYB can reach 34.5 mg/L. With the overexpression of key gene in the mevalonate pathway and the enhanced expression of the fatty acid synthesis pathway, the β-carotene titer of the engineered strain Yli-CAH reached 87 mg/L, which was 152% higher than that of the strain Yli-C . Through the further expression of the rate-limiting enzyme tHMGR and the copy number of β-carotene synthesis related genes, the β-carotene production of Yli-C2AH2 strain reached 117.5 mg/L. The final strain Yli-C2AH2 produced 2.7 g/L β-carotene titer by fed-batch fermentation in a 5.0-L fermenter. This research will greatly speed up the process of developing microbial cell factories for the commercial production of β-carotene. One-Sentence Summary: In this study, the β-carotene synthesis pathway in engineered Yarrowia lipolytica was enhanced, and the fermentation conditions were optimized for high β-carotene production. Graphical Abstract: